My middle child, there's no one like you - Leman, Kevin; Leman, Kevin, II (Grand Rapids, Mich. : Revell, 2005)
Mama Bear describes to her middle-born cub all the qualities that make her special.
"A birth order book"--Jacket.
Keywords: Bears -- Fiction; Middle-born children -- Fiction; Birth order -- Fiction; Mother and child -- Fiction